Proceedings of the Companion Publication of the 2015 Annual Conference on Genetic and Evolutionary Computation 2015
DOI: 10.1145/2739482.2768497
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Collective Behaviors by Minimizing Surprisal and by Micro-Macro Links

Abstract: Evolving collective robot behaviors is more challenging than the evolution of controllers for single robots due to multiple interactions between agents [8, 1]. However, the collective system with its microscopic (individual) level and its macroscopic (swarm) level also creates new opportunities to generate the desired behaviors. I present two of these opportunities here.First, we can leverage the robot-robot interactions to basically bootstrap the system and to trigger the emergence of complex behaviors. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Other researchers have investigated the effect of group size in the evolution of groups of simulated agents beyond predator-prey scenarios in a more general context. They find that the behavior of the group of agents and the individual agent is dependent on the group size [32, 33]. In another study which changed the group size during evolution, the authors show that it can be easier for smaller groups than larger ones to organize themselves [5].…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have investigated the effect of group size in the evolution of groups of simulated agents beyond predator-prey scenarios in a more general context. They find that the behavior of the group of agents and the individual agent is dependent on the group size [32, 33]. In another study which changed the group size during evolution, the authors show that it can be easier for smaller groups than larger ones to organize themselves [5].…”
Section: Discussionmentioning
confidence: 99%
“…Hamann [11] showed that swarm behavior in general and the type of swarm behavior in particular is dependent on the density of the swarm. In his work he used a one dimensional changing environment to influence the evolution.…”
Section: Related Workmentioning
confidence: 99%